2017
DOI: 10.1364/boe.8.003796
|View full text |Cite
|
Sign up to set email alerts
|

Method for quantitative assessment of retinal vessel tortuosity in optical coherence tomography angiography applied to sickle cell retinopathy

Abstract: Tortuosity is an important geometric vessel parameter and among the first microvascular alterations observed in various retinopathies. In the current study, a quantitative vessel tortuosity index (VTI) based on a combination of local and global centerline features is presented. Performance of VTI and previously established tortuosity indices were compared against human observers' evaluation of tortuosity. An image-processing pipeline was developed for application of VTI in retinal vessels imaged by optical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…For illustration, exemplary results are shown for tiles of 100 × 100 px (resolution: 6.5 μm). Results using the methods of Liew et al, 22 Khansari et al, 11 Chu et al, 15 Lozzi et al, 25 and OBVS are shown as segmented vessels as well as skeletons in comparison to the ground truth. background.…”
Section: Comparison Of Performancementioning
confidence: 95%
See 4 more Smart Citations
“…For illustration, exemplary results are shown for tiles of 100 × 100 px (resolution: 6.5 μm). Results using the methods of Liew et al, 22 Khansari et al, 11 Chu et al, 15 Lozzi et al, 25 and OBVS are shown as segmented vessels as well as skeletons in comparison to the ground truth. background.…”
Section: Comparison Of Performancementioning
confidence: 95%
“…Thus far, previous work in OCTA is mainly applied to images of the retinal 11,15,33 and cerebral vasculature. Both show vessel in low scattering environments.…”
Section: Optimizing Parameters Of Four Previously Used Algorithms Formentioning
confidence: 99%
See 3 more Smart Citations